Spirituality and Resilience in Cambodia: A Trauma-Informed Perspective (Global Journal of Human-Social Science, 2019)
A vast number of children and young people globally face the harsh realities of war, genocide, natural disasters and other such tragedies. Yet there is limited research and few published studies that look specifically at how spirituality can be utilized as a trauma-informed approach to promote resilience and wellbeing for young people. Earlier research conducted with teachers and clinicians working with traumatized children at Hagar International Cambodia indicated a convergence of trauma-informed themes. In particular, a religious and spiritual approach to resilience was identified as one of the key factors for children in their recovery from trauma (Wyatt, et al, 2017; 2018). Hagar is a faith-based human rights organization providing advocacy services for women and children who have survived the most extreme cases of human rights abuse (Hagar International, 2015). This research continues with young people who have been supported by Hagar, exploring the protective factors that promote wellbeing and resilience.